Aging of Polyphenylene Sulfide-Glass Composite and Polysulfone in Highly Oxidative and Strong Alkaline Environments - Zheng, X. X.; Böttger, A. J.; Jansen, K. M. B.; van Turnhout, J.; van Kranendonk, J. (Frontiers in Materials, 2020)
Alkaline water electrolysis becomes increasingly important for the supply of renewable energy, and of raw material for the chemical industry. An attractive choice for the encapsulation of the electrolyte cell is an (advanced) engineering polymer. The objective of this paper is to find a suitable one that can withstand for many years: 30 wt% KOH solution and pure oxygen at a high pressure of 50 bar and at an elevated temperature of 90°C. Using CES EduPack, 12 possible thermoplastic polymers were selected, of which polyphenylene sulfide (PPS) and polysulfone (PSU) were further investigated using accelerated testing. The polymers have been exposed to three KOH concentrations (15, 30 and 45 wt%), two oxygen pressures (pure O2 at 5 bar and air with pO2 = 20%), and three temperatures (90°C, 120°C, and 170°C). Extensive characterization of the exposed samples has been carried out using various techniques, including weight, tensile, DMA, and creep-recovery measurements, as well as DSC, FTIR, XRD and SEM. After 12 weeks of aging, glass fiber reinforced PPS failed in a strong alkaline solution at high temperatures, due to the dissolution of the glass fibers. The PPS matrix itself and PSU turned out to be resistant to thermo-oxidative and chemical degradation under the conditions tested. Only marginal changes in mechanical, visco-elastic and thermal behavior were observed, which can be ascribed to physical rather than chemical aging. In view of the brittle nature of PPS, it could be concluded that PSU is the most promising candidate for the long-term application in alkaline electrolysis. Extrapolating the data using time-temperature superposition, it is predicted that PSU will retain its integrity and mechanical properties for a period of 20 years of operation.